An Analysis Of Teachers’ Strategies In Teaching Reading Comprehension In Junior High School - Witya Chairinda Sitorus; Benni Ichsanda Rahman Hz (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The goal of this study is to identify the strategies and methods used by English teachers at junior high schools in Tanjungbalai to teach reading comprehension. This research is a combination of qualitative and quantitative research (mixed methods). Data collection techniques in this study include surveys (questionnaires), interviews, and observations. The sample for this study consisted of 10 survey and interview participants. In the implementation of the survey/questionnaire, the researcher gave questionnaires to 10 survey participants, consisting of English teachers who taught reading comprehension materials in grades 7-9. The result of this study shows that English teachers in junior high schools in Tanjungbalai apply several strategies to teaching reading comprehension in class, namely directed reading activity (DRA), reading aloud in class, and no strategy (collecting vocabulary or difficult vocabulary).